“Same Calories, Different Foods” – What do you choose? The role of construal level and age in shaping food choices - Kim, Eunho; Kang, Yoon-Hee (Frontiers in Psychology, 2025)
IntroductionHealth-related food choices are often influenced by two central attributes: food type (such as healthy vs. less healthy) and food quantity (such as large vs. small portions). Based on Construal Level Theory (CLT), this research investigates how both chronic and situational construal levels guide consumers’ attention toward these attributes and how this process varies by age. By examining decisions under caloric equivalence, the study aims to explain when and why equally caloric foods are chosen differently among consumers of different age groups.MethodsFour experiments were conducted across two main studies. Study 1A examined how individuals’ chronic construal levels, measured by the Behavioral Identification Form (BIF), influence food choices between healthy large portions and less healthy small portions of the same calories. Study 1B experimentally manipulated situational construal levels through temporal distance and tested their causal effects on food choices. Study 2A explored whether age predicts individuals’ tendency to adopt highor low-level construals. Study 2B further investigated whether attentional focus on food type versus quantity mediates the relationship between age and food choice using a nationally representative sample.ResultsAcross Studies 1A and 1B, individuals with a low-level construal were relatively more likely to focus on food quantity and select smaller portions even when these were less healthy, whereas those with a high-level construal focused on food type and preferred healthier options. Study 2A found that older adults were more likely to exhibit lower-level, concrete thinking compared to younger adults. Study 2B showed that age-related differences increased older adults’ attentional focus on food quantity, which in turn led them to choose smaller but less healthy foods. The findings collectively reveal that age affects food decisions indirectly through differences in attentional focus and construal level.DiscussionTogether, these studies integrate construal level and age within a unified framework of health-related food decision-making. The results demonstrate that construal level serves as a key psychological mechanism explaining why people of different ages make different food choices even when calorie levels are identical. This research provides valuable insights for developing age-tailored health communication strategies and designing more effective dietary interventions that account for cognitive and motivational differences across age groups.